Pathogenesis of Pregnancy-Related Complication - Hromadnikova, Ilona (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue, "Pathogenesis of Pregnancy-Related Complications", 4 reviews, 13 original papers, 1 communication, and 1 case report are compiled. These papers were published by scientific teams from 24 countries, including China, Tunisia, Canada, France, Serbia, Portugal, Spain, Chile, Singapore, Australia, the USA, Mexico, the Czech Republic, Germany, Sweden, Finland, the United Kingdom, Norway, Poland, Greece, Japan, Italy, Switzerland, and Israel, which is a really great achievement.